The supply risk of the global niobium industry chain: propagation path and impact analysis based on multi-layer network - Luo, Fanjie; Liu, Wei; Qin, Ailing; Qu, Lingfei; Liu, Qunyi (Frontiers in Earth Science, 2024)
Niobium, an irreplaceable raw material in high-tech industries, boasts a complex global trade network across its industrial chain. This study, leveraging 2022 trade data and inter-linkage dependencies within the niobium industry, constructs a multi-layer network model and simulates the impact and propagation of supply disruptions under two realistic scenarios: Restrictions on primary product exports and total export bans. Our findings reveal that: (1) Supply constraints on primary products cascade through the middle and downstream trade networks, impacting the final product layer more severely, especially for countries with limited ability to cope with disruptions. (2) China, Malaysia, Brazil, and the United States emerge as crucial risk sources, with their export restrictions potentially triggering a complete collapse of trade networks across all layers. (3) Hidden risk sources include Asian countries like Japan and Korea in the primary product layer, while European nations like the United Kingdom and Germany, despite playing a limited role in upstream disruptions, significantly influence the intermediate and final product layers. These findings underscore the importance of developing feasible systemic risk mitigation strategies, optimizing industrial structures, fostering global cooperation, and ultimately bolstering the robustness and resilience of the global niobium industry chain.